Indoline-dye immobilized ZnO nanoparticles for whopping 5.44% light conversion efficiency - Ambade, Swapnil B.; Mane, Rajaram S.; Han, Sung-Hwan; Lee, Soo-Hyoung; Sung, Myung-Mo; Joo, Oh-Shim (ELSEVIER SCIENCE SA, 2011)
Using indoline D102-dye, a whopping 5.44% light-to-electrical conversion efficiency owing to higher current density and open circuit voltage is explored for the ZnO nanoparticles (NPs)-based photoelectrode. The ZnO NPs/D102 dye structure has been designed onto indium-tin-oxide, electrons extractor, conducting and transparent substrate. The ZnO NPs of minimum [0 0 2] direction orientation compared to that of [1 0 0] and [1 0 1] directions, an indication of good charge transporting ability, with agglomerated grains of about 5-10 nm in diameters were immobilized in D102 dye for 1 h for dye loading. Low charge transport resistance and nearly 60% incident photon-to-current conversion efficiency were obtained. The results suggest that D102 dye can be potentially used for obtaining high performance ZnO-based dye-sensitized nanostructured solar cells. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: SENSITIZED SOLAR-CELLS; EXTINCTION COEFFICIENT; NANOCRYSTALLINE TIO2; HMP-2 DYE; PERFORMANCE; RECOMBINATION; ELECTRODE